Polymorphism in Mitochondrial Group I Introns among Cryptococcus neoformans and Cryptococcus gattii Genotypes and Its Association with Drug Susceptibility - Gomes, Felipe E. E. S.; Arantes, Thales D.; Fernandes, José A. L.; Ferreira, Leonardo C.; Romero, Héctor; Bosco, Sandra M. G.; Oliveira, Maria T. B.; Del Negro, Gilda M. B.; Theodoro, Raquel C. (Frontiers in Microbiology, 2018)
Cryptococcosis, one of the most important systemic mycosis in the world, is caused by different genotypes of Cryptococcus neoformans and Cryptococcus gattii, which differ in their ecology, epidemiology, and antifungal susceptibility. Therefore, the search for new molecular markers for genotyping, pathogenicity and drug susceptibility is necessary. Group I introns fulfill the requisites for such task because i) they are polymorphic sequences; ii) their self-splicing is inhibited by some drugs; and iii) their correct splicing under parasitic conditions is indispensable for pathogen survival. Here, we investigated the presence of group I introns in the mitochondrial LSU rRNA gene in 77 Cryptococcus isolates and its possible relation to drug susceptibility. Sequencing revealed two new introns in the LSU rRNA gene. All the introns showed high sequence similarity to other mitochondrial introns from distinct fungi, supporting the hypothesis of an ancient non-allelic invasion. Intron presence was statistically associated with those genotypes reported to be less pathogenic (p<0.001). Further virulence assays are needed to confirm this finding. In addition, in vitro antifungal tests indicated that the presence of LSU rRNA introns may influence the minimum inhibitory concentration (MIC) of amphotericin B and 5-fluorocytosine. These findings point to group I introns in the mitochondrial genome of Cryptococcus as potential molecular markers for antifungal resistance, as well as therapeutic targets.